(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
John Milton is agreat poet who had his deep-rooted philosophical and moral views, but heconsidered man responsible for his fall. His poetry is characterized bysublimity. Other poets have given us beauty, philosophy and romance, but nonehas given us such sublime things as Milton. In Paradise Lost Milton chose the Biblical theme of the creation,fall and redemption of man. All the events are ranged around the plucking ofthe apple. The scene of the action is universal space and the time is eternity.